Gait spatiotemporal alterations in schoolchildren with overweight or obesity: a cross-sectional study - José Omar Larios-Tinoco; Xochiquetzalli Tejeda-Castellanos; Carlos Maximiliano Sánchez-Medina; Ma. Elena Ortiz-Cornejo; Horacio Márquez-González; María de Lourdes Martín-López; Salvador Villalpando-Carrión; Claudia Gutiérrez-Camacho; José Luis Alaniz-Arcos (BMC Musculoskeletal Disorders)
Abstract Background Alterations in spatiotemporal parameters during walking modify and limit movement capacity in children with obesity. This study aimed to describe and compare the alterations in spatiotemporal parameters in schoolchildren according to body weight during all phases of walking. Methods We carried out a cross-sectional study of 94 schoolchildren aged 6 to 12 years and divided them into three study groups (normal weight, overweight, and obesity). Subsequently, we performed a gait study using a 3D motion analysis system and extracted the spatiotemporal parameters, and we compared the parameters obtained between the study groups. Results The stride length in both limbs was lower in schoolchildren with obesity compared to the overweight group, with a mean difference of 0.08 m on the right side (CI 95% 0.01–0.16; p = 0.02) and 0.09 m on the left side (CI 95% 0.01–0.17; p = 0.02); also, on the left side, the swing speed (m/s) was lower in the children with obesity than in the normal weight group, with a mean difference of 0.23 m/s (CI 95% 0.03–0.43; p = 0.01). Lastly, the step width (m) was greater in the group of schoolchildren with obesity compared to the normal weight group, with a difference of 0.05 m (CI 95% 0.01–0.09; p = 0.01). A moderate positive correlation was found between the width of the step and the weight gain, r = 0.41 (p < 0.001). However, we found a poor correlation between right stride length (m), left side swing speed (m/s), left stride length (m), and weight gain, r = 0.26 (p = 0.01), r= -0.21 (p = 0.04) and r = 0.21 (p = 0.04), respectively. Conclusions Spatiotemporal parameters such as stride length, swing speed, and step width were more altered in schoolchildren with obesity and correlated with body weight gain.